KORELASI PROGRAM PEMBINAAN KEAGAMAAN TERHADAP KECERDASAN SPIRITUAL SISWA - Khairun Nisa (Lembaga Pendidikan dan Tenaga Kependidikan (Center for Teacher Training) Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar in collaboration with Lecturer Consortium of Tarbiyah and Teacher Training, 2017)
The objective of the national education that has not been substantially achieved is to promote a generation who believe in One God and have a good character. Educational institutions which are designed to achieve this do only support students' intellectual education instead of students' spiritual well-being. Therefore, compre-hensive evaluation on the application of education through Religious Supervisory Program as a technical way should be implemented to achieve the objective of the national education. This paper analyses, the way to enhance spiritual well-being of students.